Exploring the links between human resource management and knowledge management: Organizational commitment, organizational citizenship behavior and knowledge sharing in Portuguese public organizations - Nunes, Ricardo Alexandre Rodrigues (2015)
Organizational commitment, defined as the individual attitude towards the organization, is related to a whole set of behaviors, including knowledge sharing behaviors, product from the organizational process where individuals mutually exchange their - implicit and explicit – knowledge and jointly create new knowledge, and organizational citizenship behaviors, defined as behaviors that, while not formally required by job tasks, decisivelly contribute to organizational success. In present research, we try to find the relationships between organizational commitment, knowledge sharing attitudes and organizational citizenship behaviors in portuguese public administration specific framework, exploring the links between Human Resource Management and Knowledge Management. To achieve the proposed goal, we performed a study based on a quantitative methodology, using for this purpose a sample of workers from three local portuguese public organizations. The survey questionnaire was an auto-response questionnaire, composed by items from the three different scales that operationalize the constructs explored in our theoretical research. The municipalities, portuguese local administration units, are a particular reality in portuguese public management context, with well defined particularities and evident boundaries - a delimited surface, a clearly defined intervention spectrum and a whole of available human, material and financial resources. In present Master’s Degree Dissertation in Business Administration, we were able to conclude that, despite the lack of a knowledge-sharing culture in portuguese public organization management strategies, portuguese public sector workers are willing to exhibit affective commitment and organizational citizenship behaviors, required attitudes for successful knowledge sharing. Proving that public administration workers exhibit those related behaviors and attitudes should be the starting point to transforming relatively uncompetitive public sector organizations into dynamic and knowledge-intensive learning organizations.